Mutants of Escherichia coli K-12 exhibiting reduced killing by both quinolone and beta-lactam antimicrobial agents. - Wolfson, J S (1990)
Norfloxacin, ofloxacin, and other new quinolones, which are antagonists of the enzyme DNA gyrase, rapidly kill bacteria by largely unknown mechanisms. Earlier, we isolated, after mutagenesis, Escherichia coli DS1, which exhibited reduced killing by quinolones. We evaluated the killing of DS1 and several other strains by quinolones and beta-lactams. In time-killing studies with norfloxacin, DS1 was killed 1 to 2 log10 units compared to 4 to 5 log10 units for the wild-type parent strain KL16, thus revealing that DS1 is a high-persistence (hip) mutant. DS1 exhibited a similar high-persistence pattern for the beta-lactam ampicillin and reduced killing by drugs that differed in their affinities for penicillin-binding proteins, including cefoxitin, cefsulodin, imipenem, mecillinam, and piperacillin. Conjugation and P1 transduction studies identified a novel mutant locus (termed hipQ) in the 2-min region of the DS1 chromosome necessary for reduced killing by norfloxacin and ampicillin. E. coli KL500, which was isolated for reduced killing by norfloxacin without mutagenesis, exhibited reduced killing by ampicillin. E. coli HM23, a hipA (34 min) mutant that was isolated earlier for reduced killing by ampicillin, also exhibited high persistence to norfloxacin. DS1 differed from HM23, however, in the map location of its hip mutation, lack of cold sensitivity, and reduced killing by coumermycin. Results of these studies with strains DS1, KL500, and HM23 demonstrate overlap in the pathways of killing of E. coli by quinolones and beta-lactams and identify hipQ, a new mutant locus that is involved in a high-persistence pattern of reduced killing by norfloxacin and ampicillin.